Evaluation of the Impact of Clinical, Functional and Social Factors on the Readmission of Patients with Pluripathologies - Valle Coronado-Vázquez; Mario Merino Casto; Tomás Martínez; Isidoro Durán Cortés; Jaime Galbarro; Carmen Ibáñez (Journal of Aging Research And Healthcare, 2016)
Purpose Hospital readmission of patients with pluripathologies is frequent and costly. This study describes the impact of patients’ pluripathologies, functional capacity and social complexity on readmissions during a 12-month period following hospital discharge. Methods A prospective cohort study. Monthly monitoring of 111 patients over 12 months in Hospital of Riotinto. The primary endpoint was readmission rate. Predictive variables: age, gender, hospitalizations the year before, illnesses that define the pluripathology, medication prescribed on discharge, social situation (Gijón Scale), functional state (Barthel) and cognitive impairment (Pfeiffer). Results Readmissions accounted for 21.6% of the patients surveyed. Of those readmitted, the mean age was lower than those who did not return to hospital (75.4 vs.79.6) (p=0.031), the average amount of medication prescribed greater (10.5 vs.8.7) (p=0.014), the Barthel score higher (52.5 vs.50.6) and the Gijón value lower (13.8 vs.14.6), but no results was significant. The mean survival time (without readmission) was 310.9 days (95% CI, 289.4-332.5). Category B (chronic renal disease and vasculitis) and F (diabetes with microangiopathy and artery disease) had a lower average survival time (X2=7.02; p=0.008) (X2=7.07; p=0.008). The readmission risk was hazard ratio (HR) = 3.13 (95% CI, 1.37-7.14) for category B, and HR = 3.38 (95% CI, 1.37-8.36) for category F. Conclusions There is a high proportion of readmissions among patients with pluripathologies in the year following discharge from hospital. The greater risk occurs in patients with chronic renal insufficiency and diabetes with microvascular complications. Factors that can be modified are polymedication and the proper control of patients’ diabetes.
Keywords: Hospital Readmission